Transformasi Pembiayaan Pemerintah Berbasis Non Utang dalam Perspektif Ekonomi Syariah - Marshanda Aulia Putri Ritonga; Naura Hanna Nazhifa; Dwiyana Syifa Rahmania (Veteran Economics, Management, & Accounting Review, 2025)
This study aims to analyze the potential and challenges in the implementation of non-debt financing from the perspective of Islamic economics and provide strategic recommendations for its implementation. The method used is a descriptive qualitative approach through literature studies from scientific journals, government regulations, and reports of related institutions. The results show that Islamic non-debt financing can be a strategic solution in strengthening the country's fiscal independence. However, its implementation is still faced with low Islamic financial literacy, limited regulations, and lack of technological integration. By strengthening regulations, educating the public, and encouraging digitalization, sharia-based financing has great potential in supporting inclusive and equitable national economic development. Keywords: Islamic Economics, Fiscal Justice, Sukuk, ZISWAF       Abstrak Penelitian ini bertujuan untuk menganalisis potensi dan tantangan dalam penerapan pembiayaan non utang dalam perspektif ekonomi syariah serta memberikan rekomendasi strategis implementasinya. Metode yang digunakan adalah pendekatan kualitatif deskriptif melalui studi pustaka dari jurnal ilmiah, regulasi pemerintah, dan laporan lembaga terkait. Hasil penelitian menunjukkan bahwa pembiayaan Syariah- non utang dapat menjadi solusi strategis dalam memperkuat kemandirian fiskal negara. Namun, implementasinya masih dihadapkan pada rendahnya literasi keuangan syariah, keterbatasan regulasi, dan minimnya integrasi teknologi. Dengan memperkuat regulasi, edukasi masyarakat, dan mendorong digitalisasi, pembiayaan berbasis syariah memiliki potensi besar dalam mendukung pembangunan ekonomi nasional yang inklusif dan berkeadilan. Kata kunci: Ekonomi Syariah, Fiskal Berkeadilan, Sukuk, ZISWAF